VD_FINDINFO HC / 2018 / 382 vom 27. April 2018 - VD Tribunal cantonal (2018)
CONTRAT D'ENTREPRISE GÉNÉRALE, RÉSILIATION ANTICIPÉE, PRIX DE L'OUVRAGE, MÉDIATIONSOLUTION D'UN CONFLIT | 404 CO, 82 CO, 213 CPC (CH), 59 al. 1 CPC (CH)